Critical Thinking Skills Reflected in Discussion Section of The Thesis - Wati, Refna; Taslim, Fadilla; Mahaputri, Dwi Settya; Yenti, Desfi; Susanti, Roza (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2025)
Critical Thinking skill is the ability of cognitive process in developing logical and reflective judgement about what someone believes and does and the ability to analyze and evaluate thought.Critical thinking skill will help the students to decide what sources of information that will be used to support their idea, how to interpret those infomation and organize their writing to be more logical and accurate. The Discussion section in the thesis presents and discusses the findings in details and it needs the reseacher strong argument to convince the reader about the findings. The purpose of the research is to find out and explain the six core of critical thinking skills reflected in discussion section of the thesis written by the graduate english students of Universitas Negeri Padang. The source of data in this research was 9 documents of discussion section of the thesis written by graduate English students of Universitas Negeri Padang. Descriptive using qualitative approach was used in this research. The result of this research reveal that there were 244 times critical thinking skill reflected in the 9 documents of discussion section of the theses written by graduate english students of Universitas Negeri Padang. The finding shows that the students applied four skills out of six critical thinking skills in writing discussion section of the thesis. They were explanation skill 97 times (39.75%), analysis skill 95 times (38.93%), interpretation skill 43 times (17.62%), and inference skill 9 times (3.68%). The evaluation skill and self-regulation skill did not found in this research. Those skills are important skills in writing discussion section of thesis which basically contain depth exploration of the result of the research, interpreting it, and comparing it with existing and relevant theory.